Vitamin B12 Catalysis: Probing the Structure/Efficacy Relationship. Issue 29 (30th March 2017) - Karczewski, Maksymilian; Ociepa, Michał; Pluta, Katarzyna; ó Proinsias, Keith; Gryko, Dorota
Abstract: Vitamin B12 is a cofactor for many enzymes, but it also functions as a catalyst in C−C bond‐forming reactions. Herein, the impact of corrin structural modifications on their catalytic efficacy was examined. Derivatives with various substituents at c ‐, d ‐, and meso ‐positions were synthesised by using traditional and new microwave methodologies, and then tested in the model reaction of 1, 1‐diphenylethylene with ethyl diazoacetate. To complement the experimental data, cyclic voltammetry and DFT calculations were performed. Mainly alterations at the c ‐ or d ‐positions influence both the reaction yield and selectivity. Abstract : Maximum potential of vitamins : Derivatives of vitamin B12 modified at the c ‐, d ‐, and meso ‐positions were synthesized by using new microwave methodology and tested as catalysts in the model reaction of 1, 1‐diphenylethylene with ethyl diazoacetate. The results show that mainly alterations at the c ‐ and d ‐positions influenced the catalytic efficacy of vitamin B12 derivatives (see figure).